Environmental Biotechnology. - Jogdand, S. N. (Himalaya Pub. House, 2010)
Industrial progress which has contributed to comforts and luxuries of human life will become more respectable if it maintains due regard to nature and its equilibrium. Biotechnology which has number of applications in fields of agriculture, medical, food, energy, industrial production has also its promises for environment protection. Apart from pollution control through biotreatment of wastes, Ecofriendly products and processes from biotechnology (as preventive approaches) will prove as effective options in future. This book aims to discuss `Industrial Pollution Management` as area of most con.